Studi Sistem Pentanahan Pada Transformator Daya 60 MVA di GIS 150 KV - Samsurizal Samsurizal; Kathelya Nindya Ulina; Andi Makkulau; Nurmiati Pasra (EPSILON: Journal of Electrical Engineering and Information Technology, 2021)
Grounding system is one way to reduce the effect of an electric current that can occur by several kinds of causes, such as leakage current or short circuit and the result of lightning surges. One method of grounding on a power transformer used by GIS Jatiwaringin is to use a NGR (Neutral Grounding Resistor) mounted on the 20 kV side, while on the 150 kV side it uses direct grounding (solid grounding) and the presence of a Ground Fault Relay. The value of single-phase short circuit current to the ground with resistance R = 12 Ω at the location with the percentage of disturbance of 25% that is equal to 928.48 Ω. Meanwhile, the value of single-phase short-circuit current to the ground without passing R at the location with a disturbance percentage of 25% is equal to 4066.55 Ω. Thus, the effect of the NGR on a single-phase to short-circuit fault current is to limit the one-phase short-circuit fault current to the ground so it does not flow to the neutral point of the transformer. The TMS value on the GFR on the outgoing side based on calculations is 0.11 and based on the installed relay is 0.12. Meanwhile, the TMS value on the GFR on the incoming side based on calculations is 0.27 and based on the installed relay is 0.15. Then, at the location with 25% disturbance percentage is 0.382 s. The difference between the relay's working time on the outgoing side and the incoming side is still in accordance with applicable standards, with a maximum difference of 0.4 seconds.